Развитие академического письма у студентов педагогических направлений - Tolegenova, Gulayim Jangabergenovna (SCIENCE and SOCIETY, 2026)
The article is devoted to the development of academic writing among students of pedagogical training programs. The relevance of forming scientific written competence in the context of higher education modernization is substantiated. The purpose of the research is to theoretically justify and develop methodological conditions for the formation of academic writing of future teachers. The methodological basis includes competence-based, discursive and activity approaches.
Keywords: academic writing; teacher education; written competence; scientific text; higher education; professional training